SONIC EXPERIENCES IN LOLITA, NABOKOV'S SENSORY TRAGEDY - Iglesias Quadrado, Lauro (Cadernos do IL, 2017)
Vladimir Nabokov's novel Lolita was written and published amidst intense social experiences connected to social and medial dimensions. The historical time which sets the background for the novel, the decades of mid twentieth century, presents transformed soundscapes, which count both on urban innovations and massive presence of unheard-of musical styles that begin to become popular from this moment on. Founded on this characterization, this article analyzes how the characters of the book are composed by Nabokov in a vigorous exercise of audiograph, which climaxes in sonorously dramatic scenes which benefit from readers' shared aural experience to reach its full potential.